2020
DOI: 10.3390/acoustics2020018
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Analytical Investigation of the Tonal Trailing-Edge Noise Radiated by Low Reynolds Number Aerofoils

Abstract: An experimental and analytical study of the tonal trailing-edge noise of a symmetric NACA-0012 aerofoil and of a cambered SD7003 aerofoil has been achieved. It provides a complete experimental database for both aerofoils and improves the understanding of the underlying mechanisms. The analysis stresses the high sensitivity of the tonal noise phenomenon to the flow velocity and the angle of attack. Several regimes of the noise emission are observed depending on the aforementioned parameters. The contributions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 41 publications
(92 reference statements)
4
45
0
Order By: Relevance
“…Moreover, for zero angle of attack, they found that the maximum tone can be detected if the BL reattaches just at the TE, and the decay of the tones is closely related to the laminar-toturbulent transition of the BL. Recently, Yakhina et al [10] also represented that the formed separation bubble plays an important role in tonal TE noise radiated by low-Reynolds-number airfoils. Nash et al [11] proposed a new mechanism for PVS based on a VS process.…”
Section: ) Introduction and Objectivesmentioning
confidence: 99%
“…Moreover, for zero angle of attack, they found that the maximum tone can be detected if the BL reattaches just at the TE, and the decay of the tones is closely related to the laminar-toturbulent transition of the BL. Recently, Yakhina et al [10] also represented that the formed separation bubble plays an important role in tonal TE noise radiated by low-Reynolds-number airfoils. Nash et al [11] proposed a new mechanism for PVS based on a VS process.…”
Section: ) Introduction and Objectivesmentioning
confidence: 99%
“…A possible explanation is that the instabilities lock on to the duct resonances. This would be plausible behavior, given the nature of the underlying generation mechanism [22][23][24][25] and the presence of multiple duct modes in the relevant frequency range.…”
Section: Boundary-layer Trippingmentioning
confidence: 95%
“…Laminar-instability noise can be eliminated by forcing transition in the relevant boundary layer. This may lie on either the pressure or the suction surface [22]. The situation is further complicated for a VAWT blade, as the pressure and suction surfaces alternate between outside and inside as the rotor circle is traversed.…”
Section: Boundary-layer Trippingmentioning
confidence: 99%
See 1 more Smart Citation
“…Other TE noise sources exist, such as the vortex shedding entailed by a blunted trailing edge (which also generates a strong tonal, dipolar acoustic emission), or the flow separation occurring in the early stage of stall (as opposed to the deep stall one, which rather results in noise radiating from the entire airfoil). Given its multiple components and complex physics, the airfoil trailing edge (TE) noise is still only partly understood [1][2][3], despite half a century of investigations using either experimental [1,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], theoretical [15][16][17][18][19], or computational [20][21][22][23][24][25] means.…”
Section: Introductionmentioning
confidence: 99%